Barriers and facilitators to the implementation of an evidence-based electronic minimum dataset for nursing team leader handover: A descriptive survey. Issue 5 (September 2018) - Spooner, Amy J.; Aitken, Leanne M.; Chaboyer, Wendy
Abstract: Introduction: There is widespread use of clinical information systems in intensive care units however, the evidence to support electronic handover is limited. Objectives: The study aim was to assess the barriers and facilitators to use of an electronic minimum dataset for nursing team leader shift-to-shift handover in the intensive care unit prior to its implementation. Methods: The study was conducted in a 21-bed medical/surgical intensive care unit, specialising in cardiothoracic surgery at a tertiary referral hospital, in Queensland, Australia. An established tool was modified to the intensive care nursing handover context and a survey of all 63 nursing team leaders was undertaken. Survey statements were rated using a 6-point Likert scale with selections from 'strongly disagree' to 'strongly agree', and open-ended questions. Descriptive statistics were used to summarise results. Results and discussion: A total of 39 team leaders responded to the survey (62%). Team leaders used general intensive care work unit guidelines to inform practice however they were less familiar with the intensive care handover work unit guideline. Barriers to minimum dataset uptake included: a tool that was not user friendly, time consuming and contained too much information. Facilitators to minimum dataset adoption included: a tool that was user friendly, saved time and contained relevant information. Identifying the complexities of a healthcare setting prior to the implementation of an intervention assists researchers and clinicians to integrate new knowledge into healthcare settings. Conclusion: Barriers and facilitators to knowledge use focused on usability, content and efficiency of the electronic minimum dataset and can be used to inform tailored strategies to optimise team leaders' adoption of a minimum dataset for handover.